2013
DOI: 10.1016/j.neuint.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of α-synuclein in the pathophysiology of alcoholism

Abstract: Alcoholism has complex etiology and there is evidence for both genetic and environmental factors in its pathophysiology. Chronic, long-term alcohol abuse and alcohol dependence are associated with neuronal loss with the prefrontal cortex being particularly susceptible to neurotoxic damage. This brain region is involved in the development and persistence of alcohol addiction and neurotoxic damage is likely to exacerbate the reinforcing effects of alcohol and may hinder treatment. Understanding the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 123 publications
1
11
1
4
Order By: Relevance
“…The concentration and composition of different alcohols (ethanol, methanol, and propanol) differently affected the fibrillization rate of α-synuclein 73 . Notably, recent studies have established that overexpression of α-synuclein and the consequent higher risk for developing PD is modulated by chronic long-term alcohol exposure 110 , 111 …”
Section: In Vitro Aggregation Assays Of α-Synucleinmentioning
confidence: 99%
“…The concentration and composition of different alcohols (ethanol, methanol, and propanol) differently affected the fibrillization rate of α-synuclein 73 . Notably, recent studies have established that overexpression of α-synuclein and the consequent higher risk for developing PD is modulated by chronic long-term alcohol exposure 110 , 111 …”
Section: In Vitro Aggregation Assays Of α-Synucleinmentioning
confidence: 99%
“…En el presente estudio, el incremento en la concentración de la proteína no fue estadísticamente significativo comparado con los niveles de expresión del ARNm del SNCA por varias razones: en primer lugar, las determinaciones se realizaron en compartimentos diferentes, el ARNm en lisados de células mononucleares de sangre periférica y la proteína en plasma, por lo que no necesariamente tendrían que ser concordantes, como se ha demostrado en diferentes tejidos y regiones cerebrales 4 , 8 , 9 . En segundo lugar, las diferencias podrían deberse a mecanismos de regulación postranscripcionales que impiden la traducción eficaz del ARNm 37 , 38 ; tan es así que los cambios postranscripcionales del ARNm del SNCA están regulados por la presencia de varios microARN, especialmente el mir-7 y el mir-153, que se unen a la región 3 ’ -UTR del SNCA y cuya expresión es inversamente proporcional a la expresión del ARNm y la proteína 39 , 40 .…”
Section: Discussionunclassified
“…One report detected a lower REP1 allele of the shorter type in postmortem prefrontal cortex derived from alcoholic patients, while another study demonstrated increases in the blood of the longer REP1 alleles of α-Syn expression during alcohol withdrawal and linked to craving [ 19 , 20 ]. This study demonstrated that longer alleles of REP1 led to a higher expression of α-Syn, which is associated with alcohol dependence, while the shorter alleles correlated with reduced expression of α-Syn in the dorsolateral prefrontal cortex of long-term alcoholics [ 30 , 80 ]. In fact, the drinking phase of alcoholism was associated with α-Syn promoter hyper-methylation and reduced expression [ 81 ].…”
Section: Rep1 Alleles and Variations In The 5’ And 3’utrs Of α-Synmentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) in the SNCA gene are associated with alcohol dependence, and some SNPs in the SNCA gene have been associated with alcohol craving [ 18 , 86 ]. First, a haplotype block in the 3′UTR is more abundant in individuals who crave alcohol [ 16 ], and at least 8 SNPs associated with alcoholism were found in intron 4, one of which (rs356168) was also associated with PD [ 80 ] and shown to induce subtle increases in α-Syn mRNA using CRISPR/Cas9 editing in human pluripotent stem cells (HPSCs). Following differentiation into neural cells, it was shown that this non-coding region was likely the binding site of brain-specific transcription factors EMX2 and NKX6-1 [ 87 ].…”
Section: Rep1 Alleles and Variations In The 5’ And 3’utrs Of α-Synmentioning
confidence: 99%